PENINGKATAN PENDAPATAN MASYARAKAT MELALUI BUDIDAYA SISTEMUGAKODI DI KECAMATAN GALESONGKABUPATEN TAKALAR - Dahlia, Dahlia; Narayana, Yani; Kadir, Syahriadi (Jurnal BALIRESO, 2018)
An integrated aquaculture system "UGAKODI" (udang galah, koi, dan padi or the giant prawn,koi, and paddy) is one of the alternative business that can be done to increase the communityincome. Thus, the UGAKODI system is a very potential and prospective system to be developed.This culture system has several advantages; (1) the culture of giant prawns and koi can besimultaneously conducted with rice in the paddy field, (2) this system does not require lots oflands, (3) the farmer's income can increase because the yields can not only be obtained from therice harvest but also from the prawns and koi, and (4) the farmer income cycles are more thantwice a year. Galesong District of Takalar Regency, as the location of this communitydevelopment activity, has great potential for aquaculture system "Ugakodi", because the districthas a large rice field with an abundant water source that comes from irrigation. Some of thefarmers who are partners of these activities have long been engaged in rice cultivation, but the ricefarming has not shown significant economic improvement due to low yields and the earningscycles are only twice a year. Therefore, through this system, people can optimize the agriculturalland they manage through the package of technology offered to increase the income of farmers andthe community.